The angel out of the house : philanthropy and gender in nineteenth-century England - Elliott, Dorice Williams, 1951- (Victorian literature and culture series., 2002)
"In The Angel out of the House Dorice Williams Elliott examines the ways in which novels and other texts that portrayed women performing charitable acts helped to make the inclusion of philanthropic work in the domestic sphere seem natural and obvious. And although many scholars have dismissed women's volunteer endeavors as merely patriarchal collusion, Elliott argues that the conjunction of novelistic and philanthropic discourse in the works of women writers - among them George Eliot and Elizabeth Gaskell, Hannah More and Anna Jameson - was crucial to the redefinition of gender roles and class relations."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.